2006
DOI: 10.1158/0008-5472.can-05-1865
|View full text |Cite
|
Sign up to set email alerts
|

Potent Antiandrogen and Androgen Receptor Activities of anAngelica gigas–Containing Herbal Formulation: Identification of Decursin as a Novel and Active Compound with Implications for Prevention and Treatment of Prostate Cancer

Abstract: Androgen and androgen receptor (AR)-mediated signaling are crucial for the development of prostate cancer. Identification of novel and naturally occurring phytochemicals that target androgen and AR signaling from Oriental medicinal herbs holds exciting promises for the chemoprevention of this disease. In this article, we report the discovery of strong and long-lasting antiandrogen and AR activities of the ethanol extract of a herbal formula (termed KMKKT) containing Korean Angelica gigas Nakai (AGN) root and n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
121
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 29 publications
4
121
0
Order By: Relevance
“…For various reasons, the most important of which may be public acceptance, natural products are preferred over synthetic agents for this role. In recent years, much progress has been made in identification of novel prostate cancer chemopreventive and chemotherapeutic agents from natural products (8,9,(26)(27)(28)(29)(30)(31)(32)(33)(34). It should be noted that luteolin and apigenin, two major active compounds of W. chinensis, have been independently reported as having potential for prostate cancer treatment through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For various reasons, the most important of which may be public acceptance, natural products are preferred over synthetic agents for this role. In recent years, much progress has been made in identification of novel prostate cancer chemopreventive and chemotherapeutic agents from natural products (8,9,(26)(27)(28)(29)(30)(31)(32)(33)(34). It should be noted that luteolin and apigenin, two major active compounds of W. chinensis, have been independently reported as having potential for prostate cancer treatment through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several coumarin derivatives, including decursins, decursinol, decursinol angelate, nodakenin, nodakenetin, and umbelliferone, were isolated from Angelica gigas [7,19,24]. Additional pharmacological effects of these derivatives include anti-tumor activities [2,17,22], antiplatelet aggregation [25], Helicobacter pylori-suppression [3], neuroprotection [20], and memory enhancement [21,43].…”
mentioning
confidence: 99%
“…Recently, it was shown that decursin inhibits growth and promotes cell death in both androgen-dependent and -independent prostate cancer cells (Yim et al, 2005). Jiang et al (2006) suggested that decursin inhibits the proliferation of androgen-dependent LNCaP cells reporter cells were incubated with indicated concentrations of decursinol in the presence of Wnt3a CM. After 15 h, luciferase activity was determined.…”
Section: Discussionmentioning
confidence: 99%
“…Decursin has a cytotoxic effect on leukemia cells through a mechanism involving protein kinase C and reactive oxygen species, and it has antitumor activity in mice inoculated with sarcoma cells (Lee et al, 2003b;Kim et al, 2005). It has been reported that decursin suppresses growth and promotes apoptosis in human prostate carcinoma cells (Yim et al, 2005;Jiang et al, 2006). Moreover, the (CH 3 ) 2 -CϭCH-COO-side chain of decursin, which is replaced with an OH group in decursinol, seems to be necessary for its anticancer activity (Yim et al, 2005;Guo et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation